Export and import of bamboo and bamboo products: Markov chain analysis - Jeemoni Gogoi; Ram Singh; S M Feroze; S Basanta Singh; Hehlangki Tyngkan (Agricultural Economics Research Review, 2023)
Bamboo trade has played a vital role in upliftment of socio-economic status of rural communities. This paper used trend analysis, instability index and markov chain analysis for logical inferences of the bamboo products export. The results reveal an incremental trend in area, production and productivity of bamboo, indicating ample scope for entrepreneurship development in bamboo sector. There is growth in export of bamboo products over the years however, India is still a net importer of bamboo products signifying huge scope to harness the global market.